2020
DOI: 10.21608/ejhc.2020.74781
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Program for Mothers to Protect their Children from Sexual Harassment

Abstract: Background: Sexual harassment is a real and serious problem that can affect any child or youth regardless of gender, race, religion, ethnic, age groups and occurs at all socioeconomic levels. Aim of the study was to evaluate the effect of an educational program for mothers to protect their children from sexual harassment. Research design: A quasi experimental design was used, setting: The study was conduct at Shoubra maternal and child health care center it selected randomly from Shoubra district in Cairo gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In the researchers' opinion, increasing mothers' knowledge post program had a positive influence on their attitude and in turn their practice. These results could be supported by Fatouh W et al (2020), who reported that there was a significant correlation between knowledge and behaviors of mothers' pre and post educational program. (37) Furthermore, Adel etal (2022) reported in their study that there were positive statistically significant correlations between mothers' total knowledge, total reported practices and total attitude level about protecting their children from sexual abuse.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In the researchers' opinion, increasing mothers' knowledge post program had a positive influence on their attitude and in turn their practice. These results could be supported by Fatouh W et al (2020), who reported that there was a significant correlation between knowledge and behaviors of mothers' pre and post educational program. (37) Furthermore, Adel etal (2022) reported in their study that there were positive statistically significant correlations between mothers' total knowledge, total reported practices and total attitude level about protecting their children from sexual abuse.…”
Section: Discussionmentioning
confidence: 53%
“…These results could be supported by Fatouh W et al (2020), who reported that there was a significant correlation between knowledge and behaviors of mothers' pre and post educational program. (37) Furthermore, Adel etal (2022) reported in their study that there were positive statistically significant correlations between mothers' total knowledge, total reported practices and total attitude level about protecting their children from sexual abuse. (48) Similarly, Cheraghi et al (2017) described that it was predicted that changing attitudinal behavior, practices and knowledge, would in turn result in positive parental behavior and diminish the child abuse.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…There are previous Egyptian studies implemented educational intervention for mothers to protect their children from sexual harassment. (19) (20) (21) However, the children spend a considerable time apart from their mothers and need to know how to stay safe and how to protect themselves from potential harassment situations especially the perpetrators are often known to the child. Due to the scarcity of the programs that targeting children, the current study aimed to evaluate the effect of picture-based program of on awareness of preschool children regarding self-protection from sexual harassment in response to the Egypt vision 2030.…”
Section: (18)mentioning
confidence: 99%